Effects of primary admission vs. secondary transfer to burn centers on mortality: An analysis of the German Burn Registry - Billner, Moritz; Reif, Simon; Delavari, Sarina; Grimme, Sebastian; Registry, The German Burn; Sörgel, Celena A.; Stumpfe, Maximilian C.; Breidung, David; Ehrl, Denis (Burns, 2026)
Background Severe burn injuries remain a significant challenge for healthcare systems despite major advances in treatment. While specialized burn centers play a crucial role in patient care, it remains unclear whether primary admission is associated with better clinical outcomes compared to secondary transfer. This study analyzes the impact of primary versus secondary admission on mortality using data from the German Burn Registry. Methods This study is based on prospectively collected multicenter data from the German Burn Registry. Adult patients requiring specialized burn care according to German S2k guidelines for thermal injury treatment were included. Coarsened Exact Matching (CEM) was used to adjust for baseline differences and ensure comparability between groups. Descriptive statistics and multivariate logistic regression models were applied to assess the association between admission type and mortality. Results Time from injury to admission at the burn center was significantly shorter for primary admissions compared to secondary transfers (108.77 ± 78.21 min vs. 250.43 ± 115.00 min, p ' 0.001). In univariate analysis, overall mortality was higher among patients admitted directly (13% vs. 9.9%, p = 0.014), but this effect was no longer significant after adjusting for relevant covariates. Conclusion The results indicate that primary admission to a burn center facilitates faster access to specialized care. The initially observed higher mortality among directly admitted patients may be attributed to a selection bias favoring more severe cases. This study highlights the importance of optimizing referral management to minimize delays in specialized treatment and improve outcomes for burn patients.
CRIS-Team Scopus Importer:2026-03-20
Keywords: Burn centers; Burns; Clinical outcomes; Mortality; Primary vs. secondary admission